Other Grounds: Breaking Free of the Correlationist Circle - Lindsay, David (punctum books, 2016)
Is it possible to get outside your assumptions and know the world for what it is? As the 20th century came to a close, the verdict seemed to be a resounding "no," but in recent years a renaissance in speculative thought has sparked new lines of inquiry into de-centering the human. Other Grounds enters this conversation with a decidedly lively voice and an ambitious project to match. Not only can we believe in a reality uncolored by our imaginations, says Lindsay, we can also experience it. Closely argued yet expansive in its reach, Other Grounds is built on the premise that we are by our very nature de-centered - that more than one agent is at work in the human body, and that this plurality can serve as a gateway to the experience of otherness in general. Leading the reader with a steady hand through the literature on coincident entities, set theory and the kinesthetic work of F.M. Alexander, Lindsay makes the case for the possibility of objects interceding on us from their own grounds. The result is that rare specimen in the annals of critical thought: a book that is as reasoned as it is readable, as sage as it is sardonic, and unmistakably original throughout.